Between Normality and Abnormality: Understanding the Social Support of People with Physical Disabilities Among Family - Kafaa, Kafa Abdallah (Gulawentah:Jurnal Studi Sosial, 2024)
People with physical disabilities in Indonesia face a multitude of challenges, from physical barriers to social stigmas. This study examines the complexities of how people with physical disabilities navigate these challenges, focusing on the role of social support within families. The stigma of disability is often shaped by perceptions of "normal" versus "abnormal," which deeply influence the social support of people with disabilities. By analyzing two case studies in Yogyakarta, Indonesia, this article highlights how differing family perceptions (whether they see the disability as normal or abnormal) affect the nature and effectiveness of the social support provided. The research reveals that families who view disabilities as a normal variation tend to offer more supportive environments, fostering better psychological well-being and greater participation in family life. Conversely, families who perceive disabilities as abnormal often provide less emotional support, negatively impacting the individual’s sense of belonging. This study underscores the importance of shifting societal and familial perceptions to reduce stigma and improve the quality of life for people with physical disabilities. The findings contribute to the ongoing discourse on disability inclusion and provide a foundation for policy recommendations to foster a more supportive and inclusive environment.